The fogo volcano (Cape Verde) 2014 eruption: impacts on human health - Candeias, Carla (2017)
Volcanic eruptions disturb directly and indirectly the ecosystems and the health of the exposed populations. Hazards include, among others, toxic volcanic ashes with diameters <10 μm (PM10). During volcanic eruptions and their immediate aftermath, increased respiratory system morbidity has been observed as well as mortality among those affected by volcanic eruptions. Unfavorable health effects could partly be prevented by timely application of safety measures.